Survei Minat Belajar Siswa Terhadap Pembelajaran Futsal di MAN Karawang - Ferlian Hendriana Erlangga; Abduloh; Ruslan Abdul Gani (Jurnal Literasi Olahraga, 2021)
The purpose of this study was to find out how students interest in learning futsal at MAN Karawang. One of the background problems that occured during observations at school was that the PJOK teacher had not delivered futsal learning materials, including because the teacher had not yet mastered the futsal learning materials. In solving the problem formulation in this study used a quantitative approach using survey methods. Based on the description of the data and the discusion of this research, students, interet in learning futsal at MAN Karawang is in the “Very high” category of 10.98% as many as 9 students, the “high” category of 39.02% as many as 32 students, the “medium” category amounted to 26.83% as many 22 students, the “low” category of 18.29% as many as 15 students.